An update on the role of epigenetics in systemic vasculitis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Purpose of review The purpose of this review is to discuss recent observations of epigenetic changes related to the complex pathogenesis of systemic vasculitides and their contribution to the field. Recent findings There have been new observations of epigenetic changes in vasculitis and their potential role in disease pathogenesis in antineutrophil cytoplasmic antibody-associated vasculitis, giant-cell arteritis, Kawasaki disease, Behcet's disease, and IgA vasculitis. Some of this recent work has focused on the efficacy of using DNA methylation and miRNA expression as clinical biomarkers for disease activity and how DNA methylation and histone modifications interact to regulate disease-related gene expression. Summary DNA methylation, histone modification, and miRNA expression changes are all fruitful ground for biomarker discovery and therapeutic targets in vasculitis. Current knowledge has provided targeted and suggested effects, but in many cases, has relied upon small cohorts, cosmopolitan cell populations, and limited knowledge of functional interactions. Expanding our knowledge of how these epigenetic mechanisms interact in a disease-specific and cell-specific manner will help to better understand the pathogenesis of systemic vasculitis.
Keywords: DNA methylation; epigenetics; histone modification; microRNA systemic vasculitis; BLOOD MONONUCLEAR-CELLS; DNA METHYLATION CHANGES; OCULAR BEHCETS-DISEASE; T-CELLS; UP-REGULATION; EXPRESSION; MICRORNAS; TH17; SUSCEPTIBILITY; PATHOGENESIS